2018
DOI: 10.1093/jac/dky256
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral potency of 4′-ethnyl-2′-fluoro-2′-deoxyadenosine, tenofovir alafenamide and second-generation NNRTIs across diverse HIV-1 subtypes

Abstract: Our combined virological and biochemical data suggest that EFdA inhibits both WT and reverse transcriptase inhibitor-resistant viruses efficiently in a subtype-independent manner. In contrast, HIV-1C is least susceptible to etravirine and rilpivirine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Subtype-specific differences in sensitivity and the impact of naturally occurring polymorphisms (PMs) are major emerging threats to the success of combination antiretroviral therapy (cART). In support of such subtype-specific differences, we recently reported that susceptibility to the non-nucleoside reverse transcriptase inhibitors rilpivirine and etravirine varies among subtypes [1]. Our real-life study also indicated subtype-specific differences in first-and second-line treatment failure with protease inhibitors [2].…”
supporting
confidence: 79%
“…Subtype-specific differences in sensitivity and the impact of naturally occurring polymorphisms (PMs) are major emerging threats to the success of combination antiretroviral therapy (cART). In support of such subtype-specific differences, we recently reported that susceptibility to the non-nucleoside reverse transcriptase inhibitors rilpivirine and etravirine varies among subtypes [1]. Our real-life study also indicated subtype-specific differences in first-and second-line treatment failure with protease inhibitors [2].…”
supporting
confidence: 79%
“…In addition, when comparing intracellular dNTP/rNTP concentrations to polymerase kinetic parameters, it is important to note that variation in reported Km values can arise through discrepancies in (i) template features (DNA versus RNA, sequence, length, and structure), (ii) reaction conditions (buffer components, pH, presence of all dNTPs versus one dNTP), (iii) polymerase origins (viral strains, purification methods), and (iv) modes of the polymerizations (initiation vs. elongation). Similarly, when considering nucleotide/nucleoside inhibitor efficacy, IC50 data can vary depending on viral polymerase subtypes and physiological Mg 2+ concentrations (90,137). In addition to the steady state kinetic analyses, numerous structural and mechanistic investigations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While aptly poised for ATP-mediated excision, EFdA-TP is reincorporated into the DNA almost immediately upon excision by ATP (83). This novel drug is incorporated by HIV-1 RT with a Km of 0.024-.049 µM depending on template type-DNA versus RNA-and the subtype of HIV-1 RT used in the study (83,90). The Km associated with incorporation of EFdA-TP is lower than that of the natural substrate, dATP (0.06-0.10 µM) ( Table 1).…”
Section: Likementioning
confidence: 99%
“…In vitro drug susceptibility assays showed that EFdA had significantly greater efficacy compared to other NRTIs [23]. Moreover, EFdA inhibits both WT and RTI-resistant viruses in a subtype-independent manner [25].…”
Section: La Antivirals Targeting Hiv-1 Rtmentioning
confidence: 99%